2023
DOI: 10.3390/microorganisms11041000
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals of Withania somnifera as a Future Promising Drug against SARS-CoV-2: Pharmacological Role, Molecular Mechanism, Molecular Docking Evaluation, and Efficient Delivery

Abstract: Coronavirus disease (COVID-19) has killed millions of people since first reported in Wuhan, China, in December 2019. Intriguingly, Withania somnifera (WS) has shown promising antiviral effects against numerous viral infections, including SARS-CoV and SARS-CoV-2, which are contributed by its phytochemicals. This review focused on the updated testing of therapeutic efficacy and associated molecular mechanisms of WS extracts and their phytochemicals against SARS-CoV-2 infection in preclinical and clinical studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 127 publications
0
1
0
Order By: Relevance
“…Atherosclerosis, hypertension, thrombosis, and diabetes are the primary risk factors for the development of cardiovascular diseases [ 63 ]. Lignan in sesame, Sesamin, sesamol and sesamolin due to their anti-inflammatory, antioxidant and controlling obesity related properties have been found very effective against CVD [ [64] , [65] , [66] ]. Hence any improvements in sesame seed bioactive compounds, especially in lignans will have the advantage of using plant source for curing CVD related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis, hypertension, thrombosis, and diabetes are the primary risk factors for the development of cardiovascular diseases [ 63 ]. Lignan in sesame, Sesamin, sesamol and sesamolin due to their anti-inflammatory, antioxidant and controlling obesity related properties have been found very effective against CVD [ [64] , [65] , [66] ]. Hence any improvements in sesame seed bioactive compounds, especially in lignans will have the advantage of using plant source for curing CVD related problems.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the large majority of investigations evaluating the in silico potential of plant metabolites, few studies reported in vitro anti-SARS-CoV-2 activity of plant extracts (Nair et al, 2022; Chen et al, 2023; De Araujo et al, 2023; Farooq et al, 2024; Kakimoto et al, 2024; Rodrigues et al, 2024). Certain plants with a long history of use in traditional medicine systems to manage flu syndromes, as for example Withania somnifera (L.) Dunal, Andrographis paniculata (Burm.F) Wall.ex Nees, Echinacea purpurea (L.) Moench, Artemisia annua and Nigella sativa L., have shown to be promising candidates in the search for an effective preventive or curative treatment of COVID-19 (Kolev et al, 2022; Nair et al, 2022; Nicolussi et al, 2022; Cyril et al, 2023; Ramli et al, 2023; Shanker et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Its roots, leaves, fruits and other plant parts are rich in active substances. Many studies described over 50 identified substances of Ashwagandha, among them alkaloids, flavonoids, steroidal lactones, N-containing compounds, steroids, and salts [1,15,16].…”
Section: Introductionmentioning
confidence: 99%